The Iowa Gambling Task (IGT) in Brazil: a systematic review - Rutz,André (2013)
Background: Decision-making is a complex, multidimensional cognitive function that requires the choice between two or more options and also the predictive analysis of its consequences. One of the tools most widely used to assess decision-making in neuropsychological research is the Iowa Gambling Task (IGT). Objective: To conduct a systematic review of articles reporting empirical IGT studies based in Brazil. Method: Articles were obtained from multiple journal databases including ISI Web of Knowledge, Scopus, SciELO, LILACS, and Scholar Google. Results: Thirty-six studies were included in this review and divided into four categories according to main subject matter (psychiatry & personality; demographic & cultural variables; medical/clinic; and psychometric properties & test administration standardization). In general, there was a significant growth in research employing IGT (Χ² = 17.6, df = 5, p = 0.0003), but this growth was restricted to a few geographic areas of Brazil. The psychiatry & personality subject matter was the most abundant, accounting for 14 publications (39% of the total sample). Conclusion: Since its first adaptation to Brazilian Portuguese in 2006, a growing interest in decision-making as measured by the IGT can be observed, with psychiatry & personality topics representing a large portion of the scientific inquiry to date. Nevertheless, in order to extend the initial results of Brazilian IGT decision-making research, more studies are necessary - across a more diverse range of topics, including demographic & cultural variables, and psychometric properties & test administration standardization, the areas least studied -, as is the dissemination of the IGT to more regions of the country.